2018
DOI: 10.1073/pnas.1809668115
|View full text |Cite
|
Sign up to set email alerts
|

Neural basis of location-specific pupil luminance modulation

Abstract: Spatial attention enables us to focus visual processing toward specific locations or stimuli before the next fixation. Recent evidence has suggested that local luminance at the spatial locus of attention or saccade preparation influences pupil size independent of global luminance levels. However, it remains to be determined which neural pathways produce this location-specific modulation of pupil size. The intermediate layers of the midbrain superior colliculus (SC) form part of the network of brain areas invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 52 publications
(65 reference statements)
1
19
0
Order By: Relevance
“…Preparing an oculomotor response to a probe location, which is known to recruit visual spatial attention (41, 43), also enhances the PLR to that probe (14, 29, 46, 47). Together, these results showed that the PLR scales with visual attention regardless of whether it is endogenously cued (13, 15), exogenously cued (14, 29, 48), and or recruited by saccadic preparation [Figure 1D; (14, 29, 46, 47)].…”
Section: Attention and The Pupil Light Responsementioning
confidence: 86%
See 2 more Smart Citations
“…Preparing an oculomotor response to a probe location, which is known to recruit visual spatial attention (41, 43), also enhances the PLR to that probe (14, 29, 46, 47). Together, these results showed that the PLR scales with visual attention regardless of whether it is endogenously cued (13, 15), exogenously cued (14, 29, 48), and or recruited by saccadic preparation [Figure 1D; (14, 29, 46, 47)].…”
Section: Attention and The Pupil Light Responsementioning
confidence: 86%
“…However, it was not until much later that studies began to explicitly test the idea that the PLR is modulated by selective visual attention (1315, 29, 45). For example, instructions to attend to a bright stimulus enhance the PLR to that stimulus, while instructions to attend away diminish PLR magnitude (13, 15). The PLR also tracks trial-by-trial variability in the selective attention paid to an evoking probe [Figures 1A,C; (14, 29)].…”
Section: Attention and The Pupil Light Responsementioning
confidence: 99%
See 1 more Smart Citation
“…But what exactly does the effect of semantic brightness, or of higher level cognition in general, on the PLR reflect? To test this, Ebitz & Moore (2017) applied subthreshold microstimulation to the frontal eye fields (FEF), an area of the prefrontal cortex that is involved in the control of eye movements and visual attention (see also Wang & Munoz, 2018 for a similar study on the superior colliculus). When FEF cells are stimulated strongly (suprathreshold), an eye movement is triggered to a predictable location.…”
Section: Discussionmentioning
confidence: 99%
“…21 Brightness is one of the absolute attributes of the visual sensation according to which an area appears to emit more or less light. 22 While the dependence of the pupillary diameter with luminance has been extensively investigated, [23][24][25][26] and relationship equations have been proposed between these variables, 8 this is not the case for the dependence of the pupillary diameter with brightness, a relationship that has been little studied so far. The physiological substrate of the brightness perception is not well understood.…”
Section: Introductionmentioning
confidence: 99%